REGIONAL FEATURES OF TOURISM DEVELOPMENT IN UKRAINE (INNOVATIVE ECONOMY, 2020)
Okhota V.I. REGIONAL FEATURES OF TOURISM DEVELOPMENT IN UKRAINEPurpose. The aim of the article is to systematization of scientific and methodological approaches and optimization of the methodology of evaluation systematization of the picture of regional peculiarities of tourism development in Ukraine.Methodology of research. The general and special research methods were used in the process of research, in particular: the method of systematization of scientific and methodological approaches was applied in developing the author's methodology for assessing the state, features and level of tourism development in the context of the regions of Ukraine. Assessment of the state, features and level of tourism development in the regions of Ukraine was carried out on the basis of the methodology of scoring, comparative, statistical analysis, and the ranking method.Findings. The author's methodology of express analysis of the peculiarities of the level of tourism development in the regional dimension was developed and presented. An assessment of the state of the features of the level of tourism development in the regions of Ukraine with the use of this methodology has allowed to determine the visual picture in this area of research. The basic characteristics of the number fund of the regions of the country are determined, the regions of Ukraine with the highest level of development in the estimated list of indicators of development of tourist potential are revealed.Originality. For the first time a methodical approach is proposed that provides an optimal set of valuation indicators covering the main characteristics of tourism development at the regional level; also, a formula for the characterization of the number fund has been developed according to the categories of collective means of placement, which helps to determine the visual picture in this area for each region of the country.Practical value. Using the presented development expands the scientific and methodological base of the study, allows to comprehensively assessing the state of tourism development in the regions of Ukraine.Key words: features, tourism, region, tourist potential, express analysis, number fund, methodology, collective accommodation facilities, restaurant facilities, sightseeing places.
Keywords: Key words; features; tourism; region; tourist potential; express analysis; number fund; methodology; collective accommodation facilities; restaurant facilities; sightseeing places.